(untitled) (Global Journal of Human-Social Science, 2014)
The current day development models proclaim and promise for self sufficiency and sustainability for the masses especially whenever there is a debate over rural development issue in the third world countries like Pakistan. In fact the today’s world is fast approaching the sustainable livelihood strategies which unfortunately failed to bring about the results assured. Failure of Green Revolution has made the scholars, professionals and development practitioners to repondoner the western development model particularly those promising agricultural development. The western developmental approaches basically imbedded in the capitalistic ethos resulted for radical changes while increasing the rural dependence on the urban areas and even upon the international multinational corporations. These new interventions erased the traditional self reliance of country side and thus became an indirect reason for rural urban migration. The current paper is an attempt to throw light on the effects of modern technology upon the cultural life of people of a village Sacha Soda in the district Sheikhupura of the Punjab province. The paper evaluates the indigenous people’s views on Mechanized Agricultural Methods in terms of Economic Sustainability and Cultural Compatibility.